The Role of Interferon-γ Inducible Protein-10 in a Mouse Model of Acute Liver Injury Post Induced Pluripotent Stem Cells Transplantation - Chan, Che-Chang; Cheng, Ling-Yi; Lu, Jean; Huang, Yi-Hsiang; Chiou, Shih-Hwa; Tsai, Ping-Hsing; Huo, Teh-Ia; Lin, Han-Chieh; Lee, Fa-Yauh (PLOS ONE, 2012)
Background Liver injuries are important medical problems that require effective therapy. Stem cell or hepatocyte transplantation has the potential to restore function of the damaged liver and ameliorate injury. However, the regulatory factors crucial for the repair and regeneration after cell transplantation have not been fully characterized. Our study investigated the effects and the expression of the regulatory factors in mouse models of acute liver injury either transplanted with the induced pluripotent stem cells (iPS) or the hepatocytes that differentiated from iPS cells (iHL). Methods/Principal Findings Mice received CCl4 injection and were randomized to receive vehicle, iPS, or iHL transfusions vial tail veins and were observed for 24, 48 or 72 hours. The group of mice with iPS transplantation performed better than the group of mice receiving iHL in reducing the serum alanine aminotransferase, aspartate aminotransferase, and liver necrosis areas at 24 hours after CCl4 injury. Moreover, iPS significantly increased the numbers of proliferating hepatocytes at 48 hours. Cytokine array identified that chemokine IP-10 could be the potential regulatory factor that ameliorates liver injury. Further studies revealed that iPS secreted IP-10 in vitro and transfusion of iPS increased IP-10 protein and mRNA expressions in the injured livers in vivo. The primary hepatocytes and non-parenchyma cells were isolated from normal and injured livers. Hepatocytes from injured livers that received iPS treatment expressed more IP-10 mRNA than their non-hepatocyte counter-parts. In addition, animal studies revealed that administration of recombinant IP-10 (rIP-10) effectively reduced liver injuries while IP-10-neutralizing antibody attenuated the protective effects of iPS and decreased hepatocyte proliferation. Both iPS and rIP-10 significantly reduced the 72-hour mortality rate in mice that received multiple CCl4-injuries. Conclusions/Significance These findings suggested that IP-10 may have an important regulatory role in facilitating the repair and regeneration of injured liver after iPS transplantation.